Severe Skin Lesions or Arthritis May be Associated with Coronary Artery Lesions in Kawasaki Disease - Youn, Song Ee; Ju, Hee Young; Lee, Kyung Suk; Cha, Sung Ho; Han, Mi Young; Yoon, Kyung Lim (Pediatric infection & vaccine, 2016)
Purpose: Kawasaki disease (KD) shows a variety of clinical signs of multi-system involvement, including clinical diagnostic criteria. It is unknown that the severity of the clinical signs is associated with the risk of coronary artery lesions (CALs). We wanted to evaluate clinical characteristics and the risk of CALs in the patient groups who had severe skin lesions or those with arthritis. Methods: We retrospectively reviewed the medical records of 220 KD patients who were treated with intravenous immunoglobulin (IVIG). We compared clinical and laboratory data between the group with severe skin lesions (n=52) and those with mild or no skin lesions (n=168), and between the group with arthritis (n=6) and those without arthritis (n=214). Results: The mean age of total patients was 2.23±1.87 years of age, and the male-to-female ratio was 1.5:1 (138/82). Among 220 patients, 52 patients had CALs (23.6%), and 29 patients (13.2%) showed incomplete KD. The patients with CALs had a higher mean age, longer total fever duration, and higher rate of IVIG non-responsiveness. The patient group with severe skin lesions showed a higher mean age (P<0.001), more prolonged fever duration (P=0.041), higher frequency of CALs (P=0.033), higher WBC, neutrophil, and neutrophil-to-lymphocyte ratio levels, compared to the patient group without severe skin lesions. The patients with arthritis had a tendency of further treatment with me thylprednisolone or infliximab. Conclusions: The frequency of CALs was higher in patient group with severe skin lesions. Our results suggest that the intensity of clinical signs of KD such as skin rash, cervical lymphadenopathy and possibly arthritis may be associated the risk of CALs. KCI Citation Count: 0